2011
DOI: 10.1007/s12011-011-9152-4
|View full text |Cite
|
Sign up to set email alerts
|

Altered Serum Selenium and Uric Acid Levels and Dyslipidemia in Hemodialysis Patients Could be Associated with Enhanced Cardiovascular Risk

Abstract: In the present study, the first objective was to follow up serum selenium (Se) concentrations in 117 hemodialysis patients (HPs) during a 2-year longitudinal study, relating concentrations to biochemical indexes (n = 6; namely lipoprotein profile, uric acid, and total protein levels). It was also evaluated whether the disease is associated with an enhanced cardiovascular risk. A healthy control group (n = 50) was also studied. Mean serum Se levels were significantly lower in HPs than in the controls (p = 0.002… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 33 publications
2
16
0
1
Order By: Relevance
“…In a 6-month longitudinal study with three 3-month repeated blood samplings, no statistically significant differences among the UA levels were found in 48 patients on HD (24). However, in agreement to our findings, in a 2-year study, on the basis of four 6-month blood samples, UA significantly decreased over the study period in 117 patients on HD (25). With regard to nutritional status, most of studies have shown that MHD associates with a significant decline in certain laboratory nutritional parameters, including albumin (26,27), as well as anthropometric measurements (27,28).…”
Section: Discussionsupporting
confidence: 87%
“…In a 6-month longitudinal study with three 3-month repeated blood samplings, no statistically significant differences among the UA levels were found in 48 patients on HD (24). However, in agreement to our findings, in a 2-year study, on the basis of four 6-month blood samples, UA significantly decreased over the study period in 117 patients on HD (25). With regard to nutritional status, most of studies have shown that MHD associates with a significant decline in certain laboratory nutritional parameters, including albumin (26,27), as well as anthropometric measurements (27,28).…”
Section: Discussionsupporting
confidence: 87%
“…Similarly to other diseases, a decreased Se level may be a direct or indirect consequence of renal failure, but could also exacerbate the oxidative damage, enhancing the susceptibility to complications occurring in CVD. 178 …”
Section: Renal Failurementioning
confidence: 99%
“…Hemodializált betegekben az antioxidáns hatású húgysavat is gyulladásos biomarkerként tartják számon. Krónikus vesebetegségben és veseelégtelenségben a betegségprogresszióval arányosan hyperurikaemia és szelénhiány alakul ki, amelyek egymással korrelálnak és fokozzák a cardiovascularis kockázatot [81]. A szelénpótlás hatásos lehet az oxidatív stressz csökkentésére [24,43,82,83,84].…”
Section: Szelénhiány éS Mortalitásunclassified